PERAN FREIGHT FORWARDER DALAM PERDAGANGAN INTERNASIONAL: STUDI KASUS YANG MING LINE, 2011-2016 - SELVY LEONARTO (CALYPTRA, 2018)
One way to increase the country's economic growth, that is international trade. Through international trade especially in export and import trade has an important role in enlarging market expansion and increasing foreign exchange revenue through inter-state economic cooperation. In this case to support the export and import of the country of Indonesia to grow and increase each year, it is necessary sea transport companies and freight forwarder service providers that are able to cover global trading. This research aims to observe the role of international expedition such as freight forwarder, the analysis is done by structured interview method that is used to determine the role of the company in improving the performance and the efficiency of all forms of infrastructure in supporting the export and import activities in Indonesia. The findings from this study that due to limited infrastructure from seaports in Indonesia resulted in cargo export delivery of imports decreased.